EFFECT OF AMBIENT TEMPERATURE ON MEMBRANE INTEGRITY OF SPERMATOZOA IN DIFFERENT BREEDS OF BULLS - S. R. MISHRA,; A. K. KUNDU,; A. P. K. MAHAPATRA, (The Bioscan, 2013)
The study was conducted to assess the effect of ambient temperature on membrane integrity of fresh and post thaw sperm in 4 different breeds of bulls like CB (crossbred), Red sindhi, Haryana and Jersey. Semen was collected during different temperatures throughout the year i.e. 10ºC-18ºC (lower range temperature), 25ºC-35ºC (Medium range temperature) and more than 35ºC (Higher range temperature). Membrane integrity of spermatozoa was assessed by live sperm percent count test, acrosome integrity test (AI test) and hypoosmotic swelling test (HOS test). The live sperm (%), intact acrosome (%) and HOS positive sperm (%) in all the four breeds were decreased significantly (p<0.01) with increase in temperature. During lower and medium temperature range, no significant difference was observed in live sperm (%) where as significant difference (P<0.01) was observed in acrosome integrity (%) and HOS positive sperm (%). In higher temperature range, significant difference (p<0.01).